Proposta de um modelo de avaliação de desempenho da instituição de ensino superior com enfoque em indicadores de desempenho do BSC Balanced Scorecard: caso UNIARAXA - Moço, Luiz Carlos do Espírito Santo (2007)
The aim of this work is to propose an evaluation model as a way to support the management of a non profit higher education institution, based on the indicators of performance, by using the BSC Balanced Scorecard, aiming to guarantee that the strategies and the actions which they unfold from are lined up with its mission and vision. This whole work was visualized through a context where big challenges were presented in the last decades for the management of organizations in general. Strong competition, among other factors, has motivated studies and researches about business management models for companies, including the nonprofit ones. The market related to private higher education in Brazil has experienced a strong offer expansion as a result of the perception of business opportunities in this area. Therefore, the management of higher education institutions represents a challenge to their directors, in particular the management of the private and nonprofit ones. The characteristics of such institutions demand the adaptation of the management model to the characteristics of a very competitive and distinct market regulated by the government. The starting point of this work was the review of the bibliography about the performance measurement theme. Through case study, quantitative and qualitative researches, the current management model of the institution was identified. From this point on, it was possible to identify the necessities of the institution and compare them with the performance measurement models studied. At this stage, it was possible to relate theory and practice and identify the methodology of the group on focused and choose the performance measurement model to be proposed as a management support. It was proposed a performance measurement model based on Balanced Scorecard. Five perspectives were created and the strategic objectives and the performance indicators were linked to them. With the proposition of the cause and effect relations between strategic objectives and the Strategic Map of the institution, which allow us to line up the objectives with the definite strategies, we presented the results, which served as a basis for the fulfillment of the objective of this work